2018
DOI: 10.2478/ntpe-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marine Piston Engine Injectors Dynamic State for the Non-Invasive Diagnostics Purpose

Abstract: The paper presents results of measurements conducted during multi-stage studies on injectors of WOLA 72H6 engine. The research was conducted to determine the technical condition of the injectors during their operation. As a result of the injector modeling in the CAD environment, the resonant frequencies of the examined element were obtained. The next stage of the study was a stand-alone tests with the simultaneous recording of vibration parameters. The aim of records was to link the vibration parameters with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Based on many years of diagnostic experience gathered at the Institute of Ship Construction and Operation of the Polish Naval Academy and the analysis of the available literature, an assessment of the causes of the operational unsuitability of marine engines operated in the navy was carried out (Figure 1) [4,[7][8][9][10]. The conducted analysis showed that the most frequent damage occurs in the following functional systems:…”
Section: Introductionmentioning
confidence: 99%
“…Based on many years of diagnostic experience gathered at the Institute of Ship Construction and Operation of the Polish Naval Academy and the analysis of the available literature, an assessment of the causes of the operational unsuitability of marine engines operated in the navy was carried out (Figure 1) [4,[7][8][9][10]. The conducted analysis showed that the most frequent damage occurs in the following functional systems:…”
Section: Introductionmentioning
confidence: 99%
“…The research work conducted so far, devoted to injectors and electromagnetic valves, focused on tests in regard to the fuel injector design, development of research methods, and evaluation of the injected fuel stream, but also the emissions of toxic components of exhaust gases. The authors of works [1][2][3] used measurements and analyses of vibrational signals to test fuel injectors and evaluate the quality of the injection process. In work [4], the authors applied conducted tests, a combination of qualitative imaging techniques and quantitative techniques for the determination of the drop size, such as laser diffraction and Doppler anemometry (PDA).…”
Section: Introductionmentioning
confidence: 99%